2019
DOI: 10.11603/ijmmr.2413-6077.2019.1.10306
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the New Cerebropetector Ferrum Bis(citrato)germanate at the Stage of Its Distribution to the Organs in Closed Head Injury

Abstract: Background. Previous studies showed that new coordinate compound Cerebrogerm (ferrum bis(citrato)germanate) is a promising cerebroprotector. Objective of the study is a comparative analysis of the central stage of the pharmacokinetics of Cerebrogerm as well as its distribution in vital organs in cases of closed head injury. Methods. On the experimental original model of closed brain injury in rats the parameters of the central stage of Cerebrogerm pharmacokinetics: the distribution in brain, liver,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Its biocompatibility, hydrophilicity and general safety make citric acid a common component in foodstuffs, beverages, pharmaceuticals, cosmetics, etc (Nangare et al, 2021). Recently, Varbanets and co-workers have reported that germanium coordination compounds with citric acid combined with a second metal and ligand, such as Co and 1,10phenanthroline (phen), show high antihypoxic, cerebroprotective properties and have an activation effect on enzymes (Lukianchuk et al, 2019;Gudzenko et al, 2019a,b). Complex compounds have been obtained through reactions in the system GeO 2 -H 4 Cit-CoX 2 -phen-C 2 H 5 OH-H 2 O (X = Cl, CH 3 COO).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Its biocompatibility, hydrophilicity and general safety make citric acid a common component in foodstuffs, beverages, pharmaceuticals, cosmetics, etc (Nangare et al, 2021). Recently, Varbanets and co-workers have reported that germanium coordination compounds with citric acid combined with a second metal and ligand, such as Co and 1,10phenanthroline (phen), show high antihypoxic, cerebroprotective properties and have an activation effect on enzymes (Lukianchuk et al, 2019;Gudzenko et al, 2019a,b). Complex compounds have been obtained through reactions in the system GeO 2 -H 4 Cit-CoX 2 -phen-C 2 H 5 OH-H 2 O (X = Cl, CH 3 COO).…”
Section: Chemical Contextmentioning
confidence: 99%